Edukasi HIV/AIDS Guna Mencegah Stigma dan Diskriminasi sebagai Hasil Community Diagnosis Masalah Kesehatan di Dusun Ngangkruk, Desa Pilangrejo, Nglipar, Gunung Kidul, Yogyakarta - Fitriana Putri Utami; Lia Ayu Handayani; Kiki Aliya Sofiyanti; Alisa Zulia Harmi; Nelly Nurhaliza DA; Cicilia Nindi Arsita; Nia Puspita Dewi; Maharani Yulindari; Nurul Karina Sabrina (Universitas Mathla'ul Anwar Banten, 2021)
HIV/AIDS EDUCATION TO PREVENT STIGMA AND DISCRIMINATION AS A RESULT OF COMMUNITY DIAGNOSIS OF HEALTH PROBLEMS IN NGANGKRUK HAMLET, PILANGREJO VILLAGE, NGLIPAR, GUNUNG KIDUL, YOGYAKARTA. HIV/AIDS cases are an iceberg phenomenon, with fewer people being reported than they really are. The attitude of rejection and discrimination among People Living with HIV (PLHIV) in society are influenced by many factors, one of which is knowledge of HIV/AIDS. Secondary data that has been obtained from Ngangkruk Hamlet showed that the level of knowledge about HIV/AIDS was still very low, which can lead to stigma and discrimination. Community diagnosis method carried out includes the following stages: 1.) identification of problems used the PIS-PK questionnaire, 2.) determining priority problems used USG method, 3.) selecting alternative solutions to problems using SWOT, 4.) determining priority problem solving using the effectiveness method- efficiency, 5.) problem-solving actions using HIV/AIDS education programs to prevent stigma and discrimination. Result showed that HIV/AIDS education in order to prevented stigma and discrimination was carried out by means of extension methods used power point media and posters. Assessment of information delivery was carried out using the game “who’s smart”. The responses from the participants showed good enthusiasm for the material presented.